Chirality-enhanced transport and drug delivery of graphene nanocarriers to tumor-like cellular spheroid - Jeon, Hyunsu; Zhu, Runyao; Kim, Gaeun; Wang, Yichun (Frontiers in Chemistry, 2023)
Chirality, defined as "a mirror image," is a universal geometry of biological and nonbiological forms of matter. This geometry of molecules determines how they interact during their assembly and transport. With the development of nanotechnology, many nanoparticles with chiral geometry or chiroptical activity have emerged for biomedical research. The mechanisms by which chirality originates and the corresponding synthesis methods have been discussed and developed in the past decade. Inspired by the chiral selectivity in life, a comprehensive and in-depth study of interactions between chiral nanomaterials and biological systems has far-reaching significance in biomedicine. Here, we investigated the effect of the chirality of nanoscale drug carriers, graphene quantum dots (GQDs), on their transport in tumor-like cellular spheroids. Chirality of GQDs (L/D-GQDs) was achieved by the surface modification of GQDs with L/D-cysteines. As an in-vitro tissue model for drug testing, cellular spheroids were derived from a human hepatoma cell line (i.e., HepG2 cells) using the Hanging-drop method. Our results reveal that the L-GQDs had a 1.7-fold higher apparent diffusion coefficient than the D-GQDs, indicating that the L-GQDs can enhance their transport into tumor-like cellular spheroids. Moreover, when loaded with a common chemotherapy drug, Doxorubicin (DOX), via π-π stacking, L-GQDs are more effective as nanocarriers for drug delivery into solid tumor-like tissue, resulting in 25% higher efficacy for cancerous cellular spheroids than free DOX. Overall, our studies indicated that the chirality of nanocarriers is essential for the design of drug delivery vehicles to enhance the transport of drugs in a cancerous tumor.